Marketing Strategy in Increasing Ballroom Sales at New Kuta Hotel - Monika Aprilia Wulandari; Elvira Septevany; I Gusti Agung Mas Krisna Komala Sari; I Ketut Suarta (Institut Pariwisata dan Bisnis Internasional, 2020)
This research aims to increase ballroom sales at New Kuta Hotel, to find out marketing strategies that should be used by the sales & marketing departments to increase ballroom sales and to find out which strategies are most effective in marketing strategies by sales & marketing department. The analysis techniques used are qualitative descriptive analysis, quantitative descriptive analysis, Internal Factor Analysis Summary Matrix (IFAS), External Factor Analysis Summary Matrix (EFAS), Internal–External Matrix (IE), SWOT Analysis and Quantitative Strategic Planning Matrix (QSPM). Based on the results of IFAS matrix analysis, the main strength is the ballroom sales can help increase hotel revenue, while the main weakness is the incentives imposed by the sales & marketing departments are less appropriate. Based on the EFAS matrix analysis, it was discovered that the main opportunity was the ability of sales & marketing to bring in customers while the main threat faced was the budget considered by the customer. The IE Matrix study results put the company in the Growth Strategic (Cell II) position. SWOT analysis produced eight alternative strategies of marketing strategies from the eight strategies and obtained three marketing strategies that were prioritized and calculated through QSPM Matrix with a total TAS of 181.29.